z-7-9(z-5)+5(7z+1)=

Simple and best practice solution for z-7-9(z-5)+5(7z+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-7-9(z-5)+5(7z+1)= equation:


Simplifying
z + -7 + -9(z + -5) + 5(7z + 1) = 0

Reorder the terms:
z + -7 + -9(-5 + z) + 5(7z + 1) = 0
z + -7 + (-5 * -9 + z * -9) + 5(7z + 1) = 0
z + -7 + (45 + -9z) + 5(7z + 1) = 0

Reorder the terms:
z + -7 + 45 + -9z + 5(1 + 7z) = 0
z + -7 + 45 + -9z + (1 * 5 + 7z * 5) = 0
z + -7 + 45 + -9z + (5 + 35z) = 0

Reorder the terms:
-7 + 45 + 5 + z + -9z + 35z = 0

Combine like terms: -7 + 45 = 38
38 + 5 + z + -9z + 35z = 0

Combine like terms: 38 + 5 = 43
43 + z + -9z + 35z = 0

Combine like terms: z + -9z = -8z
43 + -8z + 35z = 0

Combine like terms: -8z + 35z = 27z
43 + 27z = 0

Solving
43 + 27z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-43' to each side of the equation.
43 + -43 + 27z = 0 + -43

Combine like terms: 43 + -43 = 0
0 + 27z = 0 + -43
27z = 0 + -43

Combine like terms: 0 + -43 = -43
27z = -43

Divide each side by '27'.
z = -1.592592593

Simplifying
z = -1.592592593

See similar equations:

| -3.5x+1.3=-2.7x+1.5 | | 3(x+5)(8x-3)=0 | | 52=4y | | 4x+12=7x-15 | | 3(2y-7)=12 | | 8x+4=6x+5 | | 4x^4-53x^2+49=0 | | (3x-2)(3x-2)=16x^2 | | 145=x+x+1 | | 125c^3-1= | | -.3a+1.4=-1.2-.7a | | 11=-4r | | -11=-4r | | 5(y+2)=25 | | -11r=-4r | | -67=4x+3-7x | | 10.2x+95.31=-9.8x+95.07 | | y=x^2-5x-50 | | 14-3x=-2x+5 | | (3x-1)(x+7)=0 | | 4(x+1)=2x+12 | | 2y-1=-7 | | 4x-10=56 | | 7.5x-2.8=4.7 | | 354=x+x+4 | | 2x^2+19x+42= | | 8x^9y^3+1000= | | 3x^2+6x+5=0 | | 7x+3=2x+28 | | 0.2[x+2]+2x=6x-10 | | 4b+7b-1.6=1.2 | | 6d^2+21b=10d+35 |

Equations solver categories